Efficient Time-Domain Focussing for General Bistatic SAR Configurations: Bistatic Fast Factorised Backprojection - Rodriguez-Cassola, Marc; Prats, Pau; Krieger, Gerhard; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2010)
Due to the lack of an appropriate symmetry in the acquisition geometry, generalised bistatic SAR cannot beneﬁt from the two main properties of low-to-moderate resolution monostatic SAR: azimuth-invariance and topography-insensitivity. Precise accommodation of azimuth-variance and topography is a real challenge for efﬁcent algorithms working in the Fourier-domain, but can be quite naturally handled by time-domain approaches. We report about the ﬁrst efﬁcient and practical implementation of a generalised bistatic SAR imaging algorithm with an accurate accommodation of these two effects. The algorithm has a common structure with the monostatic fast factorised backprojection (FFBP), and is therefore based on subaperture processing. The algorithm is tested with both simulated and actual bistatic SAR data. The actual data correspond to the spaceborne-airborne experiment between TerraSAR-X and F-SAR performed in 2007. The presented approach proves its suitability for precise imaging of any given scene acquired by any given bistatic SAR conﬁguration.
DLR Import::2019-04-03